Phytogenic additives and organic acids in broiler chicken diets - Fascina, Vitor Barbosa [UNESP] (2012)
The experiment evaluated the influence of isolated or associated phytogenic additives (PA) and organic acids (OA) on nutrient digestibility, performance and carcass characteristics of broiler chickens. Two experiments were conducted in a completely randomized design with a 2 × 2 + 1 factorial arrangement of treatments (with or without PA × with or without OA + antibiotic performance enhancer and anticoccidial). In the first experiment, two metabolic tests were conducted to determine the metabolizability coefficients of the nutrients of starter and growth diets. In the second experiment, 2520 one-day-old chicks were housed in 40 experimental units to evaluate the performance and carcass characteristics. The phytogenic additives and organic acids, isolated or associated, improve the nutrient digestibility of the diet and replace the growth- promoting antibiotics. The use of organic acids isolated or associated with phytogenic additives in broiler diets improves broiler performance in comparison with free antibiotic performance enhancer at 42 days of age. Isolated or associated phytogenic additives and organic acids provided better carcass characteristics.